Regional Economic Outlook, April 2007, Asia and Pacific. (Regional Economic Outlook, 2007)
The recent economic and financial developments and trends in Asia and the Pacific are examined in this latest REO, including issues related to Asia's trade performance, notably in the high-tech sector, and the February-March bout of turbulence in the region's financial markets. The near-term outlook, key risks, and their related policy challenges are analyzed throughout, as well as in special chapters that look more closely at the evolving nature of capital inflows, housing market developments, and the impact of commodity price booms on lower-income economies.